Clinical spectrum of acute poisoning in children admitted to the pediatric emergency department - Jung Lee; Nai-Chia Fan; Tsung-Chieh Yao; Shao-Hsuan Hsia; En-Pei Lee; Jing-Long Huang; Han-Ping Wu (Elsevier, 2019)
Background: Pediatric poisoning is a common emergency worldwide. Routine surveillance is required for public health authorities and physicians to update strategies for prevention and management of pediatric poisoning. This study investigated the epidemiology of poisoning among children admitted to an emergency department (ED). Methods: This was a retrospective descriptive study. Data were collected from patients under 18 years old (y/o) presenting with poisoning at the largest ED in North Taiwan from 2011 to 2015. Results: Five-year records of 590 patients-309 (52.3%) boys and 281 (47.7%) girls-were analyzed. The mean age was 5.07 y/o (Standard Deviation [SD] = 5.02 years), and 94.7% of events occurred at home. Incidence was highest from 6 p.m. to 12 a.m. (42.2%, n = 249). Most patients younger than 11 y/o were male, but this gender distribution was reversed in adolescents (11-17 y/o). Pharmaceutical ingestion (41.4%, n = 244) was the leading cause of poisoning; pesticide was the most common non-pharmaceutical poison ingested (9.5%, n = 55). Carbon monoxide (CO) intoxication (87.6%, n = 99) and snakebite (75%, n = 9) were the common causes of inhalation (n = 113) and venom (n = 12) poisoning, respectively. The mean duration of the ED stay was 5.45 h (SD = 7.39 h), and 101 cases (17.2%), including 21 cases (3.6%) requiring intensive care, were admitted to the hospital. All patients survived. Conclusion: Most poisonings occurred in young children, at home, by unintentional ingestion of a single substance, from 6 p.m. to 12 a.m. Female adolescents were the common intentional poisoning patients and pharmaceutical ingestion was the leading cause of poisoning. This kind of information enables ED physicians to improve preparations for pediatric poisoning cases and allows public health authorities to sharpen the focus of poisoning prevention efforts. Key Words: children, emergency department, intentional, poisoning, toxicology